2016
DOI: 10.1177/0192623316668276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Toxicity Biomarkers in Rats from Different Laboratories

Abstract: There is a great need for improved diagnostic and prognostic accuracy of potential cardiac toxicity in drug development. This study reports the evaluation of several commercially available biomarker kits by three institutions (SRI, Eli Lilly and Pfizer) for the discrimination between myocardial degeneration/necrosis and cardiac hypertrophy as well as the assessment of the inter-laboratory and inter-platform variation in results. Serum concentrations of natriuretic peptides (NT-proANP, NT-proBNP), cardiac and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…It was also established by the observed histopathological alterations of cardiac tissues. CK and ANP are myocardium-specific protein reported as useful biomarkers for heart diseases [ 32 ]. Previous studies reported the increased release of CK and ANP from myocardial tissues with DOX treatment [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also established by the observed histopathological alterations of cardiac tissues. CK and ANP are myocardium-specific protein reported as useful biomarkers for heart diseases [ 32 ]. Previous studies reported the increased release of CK and ANP from myocardial tissues with DOX treatment [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…and ANP are myocardium-specific protein reported as useful biomarkers for heart diseases [32]. Previous studies reported the increased release of CK and ANP from myocardial tissues with DOX treatment [33][34][35].…”
Section: Plos Onementioning
confidence: 99%
“…At the end of treatment, the animals were treated with the anesthetic agent and a 0.8 mL sample of the ventricular intracardiac blood was collected using a sterile microsyringe (1 mL) and an EDTA Vacutainer. The cardiac natriuretic peptides NT‐proANP and NT‐proBNP were evaluated using electrochemiluminescent assays, including the Rat Muscle Injury Panel 1 Assay, Rat NT‐proANP kit K153MBD, and Rat NT‐proBNP kit K153JKD from Meso Scale Discovery (MSD, Gaithersburg, MD) 49. The serum samples were diluted 1:4 and 50 μL of diluted sample (for Rat NT‐proANP and Rat NT‐proBNP) was dispensed and tested in duplicate according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The cardiac natriuretic peptides NT-proANP and NT-proBNP were evaluated using electrochemiluminescent assays, including the Rat Muscle Injury Panel 1 Assay, Rat NT-proANP kit K153MBD, and Rat NT-proBNP kit K153JKD from Meso Scale Discovery (MSD, Gaithersburg, MD). 49 The serum samples were diluted 1:4 and 50 μL of diluted sample (for Rat NT-proANP and Rat NT-proBNP) was dispensed and tested in duplicate according to the manufacturer's protocol. After the completion of the procedure based on the MSD assay protocol, the plates were analyzed using an MSD Sector Imager, Model 2400.…”
Section: Serum Biochemistry and Electrochemistrymentioning
confidence: 99%
“…4). Especially, NeuN and Myl3 (a selective marker for myocardial cells) (Kim et al, 2016) coexpressed at cytoplasm in myocardial cells, though NeuN expressed at a lower level (Fig. 5).…”
Section: Neun Expressed At Protein Level In Different Organs Assayed mentioning
confidence: 97%